DECISION MAKING PROCESS IN CARDIAC SURGERY – CONCEPT OF BUILDING AN EXPERT SYSTEM - Tomasz HRAPKOWICZ (Management Systems in Production Engineering, 2013)
The fundamental goal of modern information technology is to support decision making process in organizations, for both routine and highly complex problems, based on heterogeneous data sources. The main objective of the paper is to present the construction concept of knowledge base for an expert system designed to support the decision making in cardiac surgery. A knowledge‐based medical expert system is designed to support decision‐making process in cardiac surgery where knowledge from medical guidelines, risk scales, and registries is applied to reason the medical procedure in a particular case scenario.